Contribution to the study of the pet dog ethogram (Canis lupus familiaris) using accelerometer collars : an experimental study - Escande, Etienne (CCSD, 2021)
In companion dogs, data on spontaneous activity are lacking in the scientific literature, due to the difficulty of finding a suitable measurement system. The use of accelerometer collars seems to represent a promising solution. The objective of our experimental study was to measure and describe the spontaneous activity of ten companion dogs, under their usual living conditions, during two two-week recording periods. Dogs were fitted with the sensor INVOXIA LWT 200 GPS TRACKER (Invoxia SAS, Issy-les-moulineaux, France), whose reliability, for this type of use was tested, on this occasion. The results show that dogs spend on average 86% of their time motionless, 7% walking and 2% running. This distribution of activity is relatively homogeneous within our sample (9/10 dogs) and is stable between the two recording periods, despite a moderate variation in the pace of life, related to the owner's activities. However, it was not possible, with our data, to distinguish the time spent at home from walking times, raising doubts about the sensitivity of the sensor to detect movement on restricted time intervals Chez le chien de compagnie, les données relatives à l’activité spontanée font défaut dans la littérature scientifique, en raison de la difficulté de trouver un système de mesure adapté. L’utilisation de colliers accéléromètres semble représenter une solution prometteuse. Notre étude expérimentale avait pour objectif de mesurer et de décrire l’activité spontanée de dix chiens de compagnie, dans leurs conditions de vie habituelles, au cours de deux périodes d’enregistrement de deux semaines. Pour cela, ils ont été équipés du capteur INVOXIA LWT 200 GPS TRACKER (Invoxia SAS, Issy-les-moulineaux, France), dont la fiabilité, pour ce type d’utilisation a été testée, à cette occasion. Les résultats montrent que les chiens passent en moyenne 86% de leur temps immobile, 7% à marcher et 2% à courir. Cette répartition de l’activité est relativement homogène au sein de notre échantillon (9/10 chiens) et est stable entre les ...